The effective bioengineering method of implantation decellularized renal extracellular matrix scaffolds - Guan, Yong (Oncotarget, 2015)
End stage renal disease (ESRD) is a progressive loss of kidney function with a high rate of morbidity and mortality. Transplantable organs are hard to come by and hold a high risk of recipient immune rejection. We intended to establish a more effective and faster method to decellularize and recellularize the kidney scaffold for transplant and regeneration. We successfully produced renal scaffolds by decellularizing rat kidneys with 0.5% sodium dodecyl sulfate (SDS), while still preserving the extracellular matrix (ECM) 3D architecture, an intact vascular tree and biochemical components. We recellularized the kidney scaffolds with mouse embryonic stem (ES) cells that then populated and proliferated within the glomerular, vascular, and tubular structures. After in vivo implantation, these recellularized scaffolds were easily reperfused, tolerated blood pressure and produced urine with no blood leakage. Our methods can successfully decellularize and recellularize rat kidneys to produce functional renal ECM scaffolds. These scaffolds maintain their basic components, retain intact vasculature and show promise for kidney regeneration.